A comprehensive review of fuzzy multi criteria decision making methodologies for energy policy making - Kaya, Ihsan; Colak, Murat; Terzi, Fulya (ELSEVIER, 2019)
Energy policy making is one of the most significant issues for countries and it can be evaluated by using multicriteria decision making (MCDM) methods. The energy decision and policy-making problems include selecting among energy alternatives, evaluating energy supply technologies, determining energy policy and energy planning. There is a wide range of studies about energy decision-making problems in the literature and different types of energy alternatives are considered in these studies. The MCDM methods are used as effective tools in order to solve energy decision-making problems since they evaluate alternatives with different perspectives in terms of several conflicting criteria. In this context, the fuzzy set theory (FST) that expresses uncertainties in human opinions, can be successfully used together with the MCDM methods to get more sensitive, concrete and realistic results. This paper aims to present a comprehensive review and bring together existing literature and the most recent advances to lead researchers about the methodologies and applications of fuzzy MCDM in the energy field. For this aim, a large number of papers that use fuzzy MCDM methods to solve energy policy and decision making problems have been analyzed with respect to some characteristics such as types of fuzzy sets, year, journal, fuzzy MCDM method, country and document type. The results of this study indicate that fuzzy Analytic Hierarchy Process (AHP), as an individual tool or by integrating with another MCDM method, is the most applied MCDM method and type-1 fuzzy sets are the most preferred type of fuzzy sets. Additionally, Turkey and China are countries which have the highest number of publications related to fuzzy MCDM methods in energy-related problems.
Keywords: Energy; Fuzzy MCDM methods; Systematic literature review; Multi-criteria decision making; PRISMA; ANALYTIC HIERARCHY PROCESS; NUCLEAR-POWER-PLANT; INTEGRATED MCDM APPROACH; SITE SELECTION; TOPSIS METHOD; TECHNOLOGY SELECTION; INFORMATION AXIOM; EVALUATION MODEL; SWOT ANALYSIS; FRAMEWORK; Energy & Fuels